2015
DOI: 10.7494/dmms.2015.9.1.9
|View full text |Cite
|
Sign up to set email alerts
|

On Public Values and Power Indices

Abstract: Abstract.In this paper, we analyze some values and power indices from a different point of view that are well-defined in the social context where the goods are public. In particular, we consider the Public Good index (Holler, 1982), the Public Good value (Holler and Li, 1995), the Public Help index (Bertini et al., 2008), the König and Bräuninger index (1998) also called the Zipke index (Nevison et al., 1978), and the Rae index (1969). The aims of this paper are: to propose an extension of the Public Help inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In general, power indices are used to measure the power of a player i in group decision-making bodies. However, the interpretation of this value— —assigned to player i changes and depends also on the measure (power index) itself and the context in which it is applied, see Felsenthal and Machover (2005) [ 32 ], Laruelle et al (2006) [ 33 ], Gambarelli and Stach (2009) [ 34 ], Bertini and Stach (2011) [ 35 ], Bertini et al (2013) [ 36 ], Bertini et al (2015) [ 37 ], Bertini and Stach (2015) [ 38 ], Stach (2016) [ 39 ], Bertini et al (2016) [ 40 ], Bertini et al (2017) [ 41 ], Bertini et al (2018) [ 42 ], Bertini et al (2020) [ 43 ], Staudacher et al (2021) [ 44 ], Stach and Bertini (2021) [ 28 ], Stach (2022) [ 30 ], Stach and Bertini (2022) [ 45 ], and Stach, Mercik, and Bertini (2023) [ 17 ].…”
Section: Notation and Definitionsmentioning
confidence: 99%
“…In general, power indices are used to measure the power of a player i in group decision-making bodies. However, the interpretation of this value— —assigned to player i changes and depends also on the measure (power index) itself and the context in which it is applied, see Felsenthal and Machover (2005) [ 32 ], Laruelle et al (2006) [ 33 ], Gambarelli and Stach (2009) [ 34 ], Bertini and Stach (2011) [ 35 ], Bertini et al (2013) [ 36 ], Bertini et al (2015) [ 37 ], Bertini and Stach (2015) [ 38 ], Stach (2016) [ 39 ], Bertini et al (2016) [ 40 ], Bertini et al (2017) [ 41 ], Bertini et al (2018) [ 42 ], Bertini et al (2020) [ 43 ], Staudacher et al (2021) [ 44 ], Stach and Bertini (2021) [ 28 ], Stach (2022) [ 30 ], Stach and Bertini (2022) [ 45 ], and Stach, Mercik, and Bertini (2023) [ 17 ].…”
Section: Notation and Definitionsmentioning
confidence: 99%
“…Bertini and Stach ( 2015 ) showed that for any simple game , for any . The minimum PHI θ index a null player i can achieve in game is shown in Theorem 5 and Corollary 3 .…”
Section: Public Help Null Player Free and Holler Indices In Comparisonmentioning
confidence: 99%
“…Thus, for any non-null players i, j ∈ N 1 , we have: Bertini and Stach (2015) showed that for any simple game v ∈ S N ,…”
Section: Proof Let Us Consider Three Simple Games Vmentioning
confidence: 99%
See 2 more Smart Citations